1996
DOI: 10.1046/j.1365-2184.1996.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative spatial distribution of in vitro‐CFCs in the bone marrow, responding to specific growth factors

Abstract: Haemopoietic progenitor cells are stimulated by a range of growth factors which promote colony growth in culture. The progenitors are a part of an age-structured developmental hierarchy in the tissue. The growth factors, although overlapping in their effects, stimulate cells preferentially at different stages in this programme. Femoral bone marrow was fractionated into axial (close to the central venous sinus) and marginal (close to the bone surface) cells. Progenitors which responded to IL-3, GM-CSF, G-CSF, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…Animal studies, however, support the hypothesis that the hematopoietic stem cells and progenitor cells are localized much closer to the bone trabecula surfaces and decrease in concentration within deeper regions of bone marrow (12,13). Work by Frassoni et al (14), Lord (15), and Cui et al (16) on the mouse femoral shaft have demonstrated a clear spatial gradient in the distribution of different cell lines responding to marrow growth factors as a function of distance into the femoral medullary cavity. The presence of a spatial gradient in hematopoietic stem and progenitor cells within human bone marrow could possibly be significant in the construction of dose-response models for marrow toxicity in cases in which the marrow absorbed dose itself is delivered nonuniformly.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Animal studies, however, support the hypothesis that the hematopoietic stem cells and progenitor cells are localized much closer to the bone trabecula surfaces and decrease in concentration within deeper regions of bone marrow (12,13). Work by Frassoni et al (14), Lord (15), and Cui et al (16) on the mouse femoral shaft have demonstrated a clear spatial gradient in the distribution of different cell lines responding to marrow growth factors as a function of distance into the femoral medullary cavity. The presence of a spatial gradient in hematopoietic stem and progenitor cells within human bone marrow could possibly be significant in the construction of dose-response models for marrow toxicity in cases in which the marrow absorbed dose itself is delivered nonuniformly.…”
mentioning
confidence: 78%
“…Although larger fields of view and 3D image analyses should be pursued to further validate the distributions shown here, it is clear that the spatial gradients seen in the mouse femur study of Cui et al (16) are also present in human bone marrow. In the mouse femur, colony-forming cells responding to IL-3 demonstrated an approximately lognormal concentration gradient with distance away from the corticomedullary interface moving toward the femoral central artery.…”
Section: Discussionmentioning
confidence: 99%
“…The recent finding that Hh pathway activity is important for growth of a significant proportion of small-cell lung cancers 7 , a tumour type not associated with Gorlin's syndrome, suggested that other, non-Gorlin's tumours might require Hh pathway activity for growth. We investigate here the role of pathway activity in tumours derived from the gut, a tissue with prominent and diverse roles for Hh signalling in developmental patterning, and in mature tissue homeostasis.…”
mentioning
confidence: 99%
“…Therefore, osteoblastic cells are a regulatory component of the haematopoietic stem cell niche in vivo that influences stem cell function through Notch activation. Niche constituent cells or signalling pathways provide pharmacological targets with therapeutic potential for stem-cell-based therapies.Mammalian bone marrow architecture involves haematopoietic stem cells (HSCs) in close proximity to the endosteal surfaces 5,6 , with more differentiated cells arranged in a loosely graduated fashion as the central longitudinal axis of the bone is approached 5,7,8 . This nonrandom organization of the marrow suggests a possible relationship between HSCs and osteoblasts-osteogenic cells lining the endosteal surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation